Split Personality Of Cobb In Inception Movie (2010) Directed By Christopher Nolan: A Psychoanalytic Approach - Prasetyo, Aris Danang (2012)
The research is proposed to analyze the split personality of Cobb's personality with Psychoanalityc Approach. The objectives of this study are to analyze the Inception movie based on Psychoanalytic approach and analyze the movie based on its structural elements. In achieving the objectives, the researcher uses descriptive qualitative method as the type of the research. The writer uses the movie of Christopher Nolan entitled Inception as the object of the study. There are two kinds of data sources used in this analyzing, namely primary and secondary data source. The primary data sources are the movie and the script of the movie itself and the secondary data sources are some books, internet and articles related to the subject. The technique of the data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. Based on the psychoanalytic analysis, in Inception, Christopher Nolan describes how traumatic experience of Cobb can cause split personality. The researcher makes an analysis of Cobb's personality. The reseacher uses the theory of Psychoanalytic by Sigmund Freud that is relevant to the problem. Based on the analysis, the outcome of this study shows that the split personality of Cobb is caused by the traumatic experience in the past.